Effects of Ga concentration in Cu(In, Ga)Se2 thin film solar cells with a sputtered-Zn(O, S) buffer layer. (15th March 2017) - Wi, Jae-Hyung; Cho, Dae-Hyung; Lee, Woo-Jung; Han, Won Seok; Chung, Yong-Duck
Highlights: Effects of Ga content on the Zn(O, S)/CIGS solar cell performance were investigated. Completed cells were annealed at 400 °C for tandem application as a bottom cell. The reverse voltage bias of QE data can distinguish influences on carrier collection. The carrier collection by change in the Ga content plays a considerable role. Abstract: Cu(In, Ga)Se2 absorbers with several different ratios of Ga/(Ga + In) were deposited by varying the Ga content using co-evaporation. The effects of Ga concentration at the surface of the CIGS on the Zn(O, S)/CIGS photovoltaic performance were investigated. Considering application as the bottom cell in a monolithic tandem structure, the optimum Ga/(Ga + In) ratio of approximately 0.26 led to the best efficiency of 14.56%, and to complete carrier collection at long wavelengths. In addition, the degradation rate in efficiency was lowest at an annealing temperature of 400 °C. The reason for losses of other Ga/(Ga + In) ratios (0.33 and 0.36) at longer wavelengths might be due to interface recombination, possibly aided by conduction band offset with the Ga grading shape by varying the Ga concentration. The results suggested that the decrease in efficiency might be due to recombination at the interface between the Zn(O, S) and CIGS layers before/after annealing. The reverse bias effect during quantum efficiency measurements at long wavelengths was used to determine separate optical and electrical losses.